THE ROLE OF PSYCHOLOGICAL SAFETY IN THE PERCEPTION OF ORGANIZATIONAL CRISIS BY EMPLOYEES (ON THE EXAMPLE OF RA LABOR MARKET) - Gevorgyan, Anahit (Modern Psychology, 2024)
In recent years the role of psychological safety in organizations has been studied by authors(A. Edmondson(1999, 2014, 2019); A.Carmeli, D. Brueller, J. Dutton(2008); A. Carmeli, R. Reiter-Palmon, E. Ziv(2010); W.A. Kahn(1990); B. Sanner, J. Bunderson(2013)) and organizations’ management teams. It has a significant impact on a number of processes within organization. The aim of this work is to study the possible influence of psychological safety on the process of employee perception of organizational crises and their readiness to overcome it. According to results, there is a positive correlaton between these two variables, a relationship in which if one variable increases the second one increases as well. As a result, in psychologically more safe environment employees have positive attitude towards organizational crises and are better positioned to deal with them. The usage of the data from this study will enable the leadership team to develop effective management approaches for managing pre-crisis and crisis situations and maintain a high level of employee engagement.
Keywords: Psychological safety; Organizational crisis; Employee engagement; Human resources; Personnel management